FRANCUSKIE PRAWO HANDLOWE NA PRZEŁOMIE XIX I XX WIEKU. KODEKS HANDLOWY NAPOLEONA Z 1807 R. A JEGO DEKODYFIKACJA - Klimaszewska, Anna (Zeszyty Prawnicze, 2016)
French Commercial Law at the Turn of the XXth Century. The Code of Napoleon from 1807 and its Decodification Summary The French „Code de Commerce” of 1807 is one of five legal acts known as the great napoleonian codifications. They have been created in the spirit of the quest for the ideal modern legislation that was supposed to last as long as possible. Unfortunately unlike the „Code Civil” the „Code de Commerce” in its original form lasted only 30 years. This was owed to many various factors related to the code itself but also the legal doctrines of the time and the socio-economical environment in which it was created. As a result it has undergone the so called „process of decodification” involving a shift of code matter from the code itself into other legal acts.